Positive parenting : protect children from the hazard of gadgets - Dewi, Ika Sari; Rahmawati, Etti; Nazriani, Dina; Meutia, Amalia; Siregar, Suri Mutia (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Technological developments have colored every aspect of life in various age levels. The age group of children belongs to a group that is vulnerable to the development of these technologies, especially the use of gadgets. Rational and age-appropriate gadget usage is one way to overcome the impact of using gadgets. This community service program aims to provide information and skills on how to deal with or handle the use of gadgets for children. This program is carried out with the delivery of 4 (four) materials through lectures, focus group discussions, and role play. Four material presented are: introduction to children's growth and development, the impact of gadgets, how to recognize the behavior of children who are addicted to gadgets, and design activities to make children avoid gadgets. The results of data analysis of the tests before and after the implementation of the program showed information about child growth and development which contributed 21.66% in increasing parents 'and teachers' knowledge of their children's development, information about the dangers of gadgets contributed 40.75% in increasing the knowledge of parents and teachers, and information about positive parenting has a very significant role of 46.05% in increasing the knowledge of parents and teachers towards positive parenting.